The nanosyntax of Hungarian postpositions - Dékány, Éva (Nordlyd, 2009)
This article considers evidence for a Nanosyntactic approach to language from Hungarian PPs. Hungarian postpositions can be divided into classes: those which take a complement without morphologically visible case (dressed postpositions), and those which take an oblique complement (naked postpositions). This paper argues that in narrow syntax, both types of postpositions subcategorize for a KP complement. The difference between the two classes is captured in terms of the amount of structure they spell out. Dressed postpositions spell out both material in the P-domain and K, thus no Case is needed or possible on the complement, while naked postpositions spell out only material in the P-domain but not K, therefore their complement needs case. It is shown that from the proposed lexical representations an empirically motivated and insightful analysis of Hungarian postpositions ensues, which elegantly captures the different word-order possibilities of the two classes.